Dismutation of Tricyanoboryllead Compounds: The Homoleptic Tetrakis(tricyanoboryl)plumbate Tetraanion. Issue 24 (19th April 2022) - Häring, Mathias; Kerpen, Christoph; Ribbeck, Tatjana; Hennig, Philipp T.; Bertermann, Rüdiger; Ignat'ev, Nikolai V.; Finze, Maik
Abstract: A series of unprecedently air‐stable (tricyanoboryl)plumbate anions was obtained by the reaction of the boron‐centered nucleophile B(CN)3 2− with triorganyllead halides. Salts of the anions [R3 PbB(CN)3 ] − (R=Ph, Et) were isolated and found to be stable in air at room temperature. In the case of Me3 PbHal (Hal=Cl, Br), a mixture of the anions [Me4− n PbB(CN)3 n ] n − ( n =1, 2) was obtained. The [Et3 PbB(CN)3 ] − ion undergoes stepwise dismutation in aqueous solution to yield the plumbate anions [Et4− n PbB(CN)3 n ] n − ( n =1–4) and PbEt4 as by‐product. The reaction rate increases with decreasing pH value of the aqueous solution or by bubbling O2 through the reaction mixture. Adjustment of the conditions allowed the selective formation and isolation of salts of all anions of the series [Et4− n PbB(CN)3 n ] n − ( n =2–4) including the homoleptic tetraanion [PbB(CN)3 4 ] 4− . Abstract : Tricyanoborylplumbate anions have been obtained and isolated as thermally robust salts. The tetrakis(tricyanoboryl)plumbate tetraanion [PbB(CN)3 4 ] 4− was obtained from [EtPbB(CN)3 ] − by stepwise dismutation in water or hydrochloric acid via [Et2 PbB(CN)3 2 ] 2− and [EtPbB(CN)3 3 ] 3− .